2004
DOI: 10.1002/hep.20260
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 inhibits the growth and invasiveness of hepatocellular carcinoma cells via protein kinase A activation

Abstract: Hepatocellular carcinoma (HCC) is a common human malignancy. Its high mortality rate is mainly a result of high intrahepatic recurrence and portal venous invasion (PVI). We previously reported that the development of PVI is related to levels of des-gamma-carboxy prothrombin (DCP), a serum protein that increases at a notably higher rate in patients with HCC. Because DCP is produced by a vitamin K shortage, we examined the biological effects of extrinsic supplementation of vitamin K 2 in HCC cells in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 45 publications
4
109
2
2
Order By: Relevance
“…The safety, relatively low cost, and ease of use make vitamin K 2 a suitable candidate for clinical trials that assess the value of combination of chemoprevention or chemotherapy in at-risk patients or in patients with a confirmed diagnosis of HCC [116,[122][123][124][125].…”
Section: Vitamin Kmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety, relatively low cost, and ease of use make vitamin K 2 a suitable candidate for clinical trials that assess the value of combination of chemoprevention or chemotherapy in at-risk patients or in patients with a confirmed diagnosis of HCC [116,[122][123][124][125].…”
Section: Vitamin Kmentioning
confidence: 99%
“…Otsuka et al [123] examined the biological effects of extrinsic supplementation of vitamin K 2 in HCC cells in vitro and in vivo. Administration of vitamin K 2 to nude mice inoculated with liver tumor cells reduced both tumor growth and weight loss.…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 99%
“…VK2 has been reported to show anticancer effects inducing apoptosis and cell cycle arrest in several tumor cell types such as leukemia cells, osteosarcoma cells, HCC cells, glioma cells, and lung cancer cells, also a number of striking anecdotal clinical reports supports use of VK2 as an anticancer agent (7)(8)(9)(10)(11)(12)(13)22). However, therapies combining VK2 with established anti-tumor agents have not been investigated.…”
Section: Discussionmentioning
confidence: 96%
“…Cell cycle arrest and apoptosis are believed to be involved in this action of VK2, but precise molecular mechanisms underlying VK2-induced growth inhibition and killing in HCC cells remain to be elucidated. Recently VK2 also was found to inhibit hepatoma cell invasiveness and metastasis (11). More importantly, we recently demonstrated that administration of VK2 to HCC patients significantly decreased recurrence of HCC after curative local ablation therapy (12).…”
Section: Introductionmentioning
confidence: 96%
“…The biological significance of this has never been clear, but it has recently been suggested that immature prothrombin or DCP has HCC growth promoting properties (Suzuki et al, 2005). This led us to consider that mature prothrombin, a major vitamin K-dependent blood coagulation factor, might also have growth regulatory properties, since K vitamins have previously been shown to have growth inhibitory activities (Yoshida etal., 2003;Otsuka et al, 2004;Lamson and Plaza, 2003;Wang et al, 1995;Nishikawa et al, 1995;Hitomi et al, 2005;Bouzahzah et al, 1995) in addition to their well-described physiological effects as cofactors for several blood coagulation proteins (such as prothrombin and factors VII, IX and X).…”
Section: Introductionmentioning
confidence: 99%